Nuts, hexagonal, self-locking, with counterbore and captive washer, with MJ threads, classifications: 1100 MPa (at ambient temperature)/235°C, 1100 MPa (at ambient temperature)/315°C, 1100 MPa (at ambient temperature)/425°C. Dimensions. (15th April 1999) - British Standards Institution,
No abstract available